GENESIS OF KARELIAN SHUNGITE WITH REFERENCE TO ITS DISTINCTIVE STRUCTURAL FEATURES - Berezkin V.I. (My University, 2001)
Structural data on shungite-bearing rocks were used to develop a new model for their nanostructure and the natural processes of their genesis and evolution. A conclusion was made that the natural solid carbon of shungite is composed of carbon black particles in a fossilized tarlike hydrocarbon matrix. Both were produced by the burning of deep-seated methane in oxygen-deficient environments. The total amount of the burned-out gas was assayed at 10*10^9 t. The gas escape was accompanied by hydrotherms with other compounds, which produced the mineral components of shungite rocks. It is hypothesized that shungite may be underlain by rocks containing hydrocarbons, which were preserved, in a certain form, to the present.